2024
DOI: 10.1021/acs.jpclett.4c00310
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency and Ultra-Stable Cesium–Bismuth-Based Lead-free Perovskite Solar Cells without Modification

Jin Huang,
Hao Wang,
Chunliang Jia
et al.

Abstract: Perovskite solar cells (PSCs) have become a new photovoltaic technology with great commercial potential because of their excellent photovoltaic performance. However, the toxicity and poor environmental stability of Pb in Pbbased perovskites limit its large-scale application. Exploring alternatives to Pb is an available approach to develop environmentally friendly PSCs. As an adjacent element of Pb, Bi shows many similar physical and chemical properties; therefore, it is commonly applied for B site substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Thin films of CsBiSCl 2 were used as solar absorber in photovoltaic devices yielding a power conversion efficiency above 10% and long-term stability at ambient conditions, suggesting a highly promising alternative to Pb halide perovskite photovoltaics . The preparation of CsBiSCl 2 chalcohalide perovskite was reported as the result of depositing and annealing a mixture of an ammonium Bi sulfide compound with CsCl in polar solvents . We find that a straightforward identification of the reaction products remains, in our opinion, elusive, in analogy to previous reports on the synthesis of other AM­(E,X) 3 compounds. …”
supporting
confidence: 55%
See 3 more Smart Citations
“…Thin films of CsBiSCl 2 were used as solar absorber in photovoltaic devices yielding a power conversion efficiency above 10% and long-term stability at ambient conditions, suggesting a highly promising alternative to Pb halide perovskite photovoltaics . The preparation of CsBiSCl 2 chalcohalide perovskite was reported as the result of depositing and annealing a mixture of an ammonium Bi sulfide compound with CsCl in polar solvents . We find that a straightforward identification of the reaction products remains, in our opinion, elusive, in analogy to previous reports on the synthesis of other AM­(E,X) 3 compounds. …”
supporting
confidence: 55%
“…In addition, an experimental study recently reported the first synthesis of CsBiSCl 2 . Thin films of CsBiSCl 2 were used as solar absorber in photovoltaic devices yielding a power conversion efficiency above 10% and long-term stability at ambient conditions, suggesting a highly promising alternative to Pb halide perovskite photovoltaics . The preparation of CsBiSCl 2 chalcohalide perovskite was reported as the result of depositing and annealing a mixture of an ammonium Bi sulfide compound with CsCl in polar solvents .…”
mentioning
confidence: 97%
See 2 more Smart Citations